Antecedents of Repurchasing Intentions of Electronic Commerce in Thailand - จันทะเสนา ฉันธะ (Human Resource and Organization Development Journal, 2019)
The present study examined the e-commerce repurchasing intention of customers in Thailand. The model proposed two main lines of antecedent factors related to repurchasing intentions. The first line consisted of e-service quality, e-satisfaction, e-loyalty and repurchasing intention which were based on the expectation-confirmation theory and self-determination theory. The second line consisted of e-service quality, e-trust and repurchasing intention which were based on the Reasoned Action Theory. The study used a consistent partial least squares structural equation model. The hierarchical component model of e-service quality was constructed based on a Reflective-reflective model. The results showed that, in second order constructs, the efficiency, system availability, fulfillment, privacy and reliability all performed well to reflect the e-service quality. The determinants that defined the effect of repurchasing intention were e-service quality, e-trust and e-satisfaction with e-loyalty not being significantly related to it. The best antecedent of repurchasing intention was e-service quality because it had a significant positive effect on all antecedent factors including repurchasing intention.